Penerapan Teknik Self Management dalam Konseling Kelompok untuk Meningkatkan Kemampuan Management Waktu Belajar Siswa Kelas VII C SMP Labschool Unesa 3 Surabaya: Implementation of Self Management Techniques in Group Counseling to Improve Time Management Skills of Class VII C Students of SMP Labschool Unesa 3 Surabaya - Izzaty Nur Fajriyah; Ari Khusumadewi (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
Problems that often occur at SMP Labschool Unesa 3 experienced by seventh grade students, especially in terms of not paying attention to the teacher's explanation during the learning process. It is known from the results of data collection that 40% of students are often late in submitting assignments and sometimes also late for school and often play cellphones when in class so that it greatly affects student achievement in class. After observing many students who are less able to manage study time with their play, as for the things that influence the lack of students in managing study time well are students often choose to play rather than study, students often procrastinate their work, students often stay up at night, students are less able to manage time well. This factor causes students to often procrastinate and students are overwhelmed in doing all the assignments given by their teachers and decreasing student achievement. The purpose of this research is the application of Self Management Techniques in group counseling to improve the ability to manage study time of students in class VII C SMP Labschool Unesa 3 Surabaya City. In this study using observation and questionnaire methods. This study used 2 cycles using pretest and postest, The results obtained in cycle 1 average learning saturation was 82.4 and the average learning saturation in cycle 2 was 57.16. So it can be concluded that group counseling with Self-management techniques can improve students' study time management skills.